PENGARUH KERAGAMAN PRODUK DAN KUALITAS PELAYANANTERHADAP KEPUTUSAN PEMBELIAN ULANGMELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING (Studi pada Konsumen Gelael Mall Ciputra Semarang) - Mayo Budi Utama; Ngatno Ngatno (Jurnal Ilmu Administrasi Bisnis, 2017)
Growth retail business a rapid progress in a few years make competition is tight. Consumer behavior in a shop at a outlet influenced by several factors of them are the diversity products and the quality of services. Supermaket Gelael Mall Ciputra Semarang is one of the supermarkets known in Semarang city. Problems in this research s a reduction turnover income Supermarkets Gelael Ciputra Semarang in 2015, impact on the number of monthly transactions in the growth supermarkets other Semarang city.This study aims to to find out whether is the products diversity and quality service of the decision the purchase repeated through customer satisfaction on the consumer Supermarkets Gelael Ciputra Semarang. Data collection techniques used the interview and questionnaires , while the sample techniques used non probability of sampling with 100 the total sample. Data in analysis with system validity test, reliability test , the coefficients determination test, simple linear regression, multiple linear regression, t test and f test , sobel test and path analysis. Analysis of data done quantitatively on the SPSS program version 19.0.The result showed that diversity of products and quality of services have a positive influence and significant of the decision re purchase through customer satisfaction. This can be seen from the results of the simple analysis linear regression, multiple linear regression, t test , f test, the coefficients determination test , sobel test and path analysis. Customer satisfaction as variable intervening mediate between the diversity of the decision to buy them are full mediation As well as customer satisfaction as variable intervening mediate between product diversity of the decision repeated purchases that is both partial mediation. Of the result of this research,Companies should improve the diversity of products and services to consumer to the customer satisfaction and will may make it a cause loyal to buy replenished so it the sale of company can increase.